New trends in criteria indicative of neoadjuvant oncological therapy of lower and middle rectal cancers - Kukučka, Martin; Danihel, Ľudovít; Oravský, Milan; Rajčok, Matúš; Bernadič, Michal; Kovarova, Paula; Birknerova, Natalie; Cerny, Marian; Novisedláková, Mária; Drahokoupilová, Miriam; Stefanik, Peter; Schnorrer, Milan (Bratislavské lekárske listy, 2023)
The indication for primary surgical resection or neoadjuvant therapy in lower and middle rectal cancers is often disputable. The aim of the study was to evaluate the occurrence of local recurrence of rectal cancer as for a period of at least 4 years after radical resection. The second aim was to evaluate and compare the results of preoperative magnetic resonance (MR) staging with definitive histology. From September 2013 to December 2017, we, at the 3rd Surgical Department Comenius University, Bratislava, prospectively evaluated patients with lower and middle rectal cancers with the distal tumor border being in a 12-cm distance from the anal verge. All patients underwent MR examination at the same MRI department and were operated on at the 3rd Surgical Department, Comenius University, Bratislava. Inclusion criteria included parameters based on MRI examination, i.e., T-staging of T1-T3b, negative extramural vascular infiltration (EMVI), negative circumferential margin (CRM), no mesorectal fascia infiltration with a distance of more than 2 mm. We did not take lymph node staging into account in the indication for primary surgical resection. We performed a radical primary resection procedure (R0 resection) in all patients. The group consisted of 87 patients, of whom 49 were men and 38 were women. The mean age of the patients was 66 years (min. 36 – max. 86 years). Our study also shows significant differences in preoperative T and N staging as compared to definitive histology. The incidence of local recurrence during a period of at least 4 years after surgery was 6.76 %. Study also shows that the indication for preoperative radiotherapy for lower and middle rectal cancers based on N status is inaccurate and leads to unnecessary indications for preoperative radiotherapy which may decrease the patients ́ quality of life and increase the post‐operative complications. We have also shown that leaving out the N-based radiotherapy from indications does not lead to an increase in the number of local recurrences in lower and middle rectal cancers (Tab. 1, Fig. 5, Ref. 22).